How our schools can be more synergic: determining the obstacles of teamwork - Karakus, Mehmet; Toremen, Fatih (Emerald Group Publishing Ltd, 2008)
Purpose - The main purpose of this study is to find out the importance levels of obstacles to teamwork in the view of teachers and thus inspire school leaders to remove these obstacles and to make teamwork more effective. Design/methodology/approach - A survey-based descriptive scanning model was used. This study was performed in Elazig city centre during the 2006-2007 academic year. A four-dimensional and 32-itemed ordering questionnaire was administered to 424 teachers working at primary schools. Findings - In the light of related literature, the most significant factors for the effectiveness of teamwork have been classified in four dimensions. These are leadership actions, structural characteristics of work group, individual characteristics of members, and interrelationships among members. Administrators' inequitable applications, lack of a group climate in which each teacher is appreciated and valued, teachers' lack of motivation, competitive and not cooperative relationships were sorted by teachers as being the most important obstacles to teamwork. There were meaningful differences among teachers' views according to the gender and tenure variables. Research limitations/implications - Since teamwork is a necessity for school effectiveness, it is very important to determine and to remove the obstacles on the way to effective teamwork. Practical implications - The study gives cues for school leaders on how teachers should be treated in general and in the aspects of their personal characteristics to attain effective teamwork in schools. Originality/value - With an original classification of the components of effective teamwork, the study seeks to determine teachers' perceptions about the importance level of obstacles of effective teamwork through an ordering questionnaire in a different perspective.
Keywords: Team working; Cultural synergy; Schools; Leaders; Teachers